ANALISA KEHILANGAN ENERGI PADA BOILER PABRIK KELAPA SAWIT ENERGY LOSS ANALYSIS ON THE PALM OIL MILL BOILER - Zulham Effendi; Zakwan; Amar Fauzi Nainggolan (Jurnal Agro Fabrica, 2020)
The purpose of this paper is to calculate boiler performance by knowing energy losses during uap production.Technical analysis on the boiler is needed, as an effort to increase efficiency and know how much energy iswasted as a loss. Factors causing the greatest heat loss / heat loss in the boiler include: "heat loss due to dryflue gas, uap content in the flue gas, water content in fuel, water content in air supply and others". Heat loss /heat loss or also can be called energy loss is one of the important factors that is very influential in identifyingthe efficiency of the boiler.For that analysis study is carried out with the calculation of heat loss in order todetermine the magnitude of performance decline and the causes of decreased performance. Based on data andanalysis of the direct method it is known that the highest energy loss is 26.6% with an efficiency of 74.5%.There needs to be an improvement in the control of the fuel settings and the incoming air optimally by usingthe Oxygen Trim Control which functions to measure the oxygen concentration in the chimney andautomatically regulates the oxygen in the air entering the burner so as to produce combustion with optimalefficiency. And by using an economizer on preheating feed water temperature can increase boiler efficiency